Posttranslational Phosphorylation and Ubiquitination of the Saccharomyces cerevisiae Poly(A) Polymerase at the S/G(2) Stage of the Cell Cycle - Mizrahi, Neptune (American Society for Microbiology, 2000)
The poly(A) polymerase of the budding yeast Saccharomyces cerevisiae (Pap1) is a 64-kDa protein essential for the maturation of mRNA. We have found that a modified Pap1 of 90 kDa transiently appears in cells after release from α-factor-induced G(1) arrest or from a hydroxyurea-induced S-phase arrest. While a small amount of modification occurs in hydroxyurea-arrested cells, fluorescence-activated cell sorting analysis and microscopic examination of bud formation indicate that the majority of modified enzyme is found at late S/G(2) and disappears by the time cells have reached M phase. The reduction of the 90-kDa product upon phosphatase treatment indicates that the altered mobility is due to phosphorylation. A preparation containing primarily the phosphorylated Pap1 has no poly(A) addition activity, but this activity is restored by phosphatase treatment. A portion of Pap1 is also polyubiquitinated concurrent with phosphorylation. However, the bulk of the 64-kDa Pap1 is a stable protein with a half-life of 14 h. The timing, nature, and extent of Pap1 modification in comparison to the mitotic phosphorylation of mammalian poly(A) polymerase suggest an intriguing difference in the cell cycle regulation of this enzyme in yeast and mammalian systems.